2021
DOI: 10.3390/healthcare9040405
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of On-Call CT Reporting in Teleradiology Networks in Comparison to In-House Reporting

Abstract: (1) Background: We aimed to compare the accuracy of after-hours CT reports created in a traditional in-house setting versus a teleradiology setting by assessing the discrepancy rates between preliminary and final reports. (2) Methods: We conducted a prospective study to determine the number and severity of discrepancies between preliminary and final reports for 7761 consecutive after-hours CT scans collected over a 21-month period. CT exams were performed during on-call hours and were proofread by an attending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Compared to in-house reporting, those who use the teleradiology system may not have access to the clinical data or previous examinations that can assist radiologists in image interpretation and impact the quality of radiology reports. 32 Several studies have discussed the link between a lack of clinical information and the diagnostic accuracy of reports. 33 , 34 Nevertheless, Storjohann et al 32 (2021) found that the absence of clinical information did not negatively impact the accuracy of radiological reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to in-house reporting, those who use the teleradiology system may not have access to the clinical data or previous examinations that can assist radiologists in image interpretation and impact the quality of radiology reports. 32 Several studies have discussed the link between a lack of clinical information and the diagnostic accuracy of reports. 33 , 34 Nevertheless, Storjohann et al 32 (2021) found that the absence of clinical information did not negatively impact the accuracy of radiological reports.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Several studies have discussed the link between a lack of clinical information and the diagnostic accuracy of reports. 33 , 34 Nevertheless, Storjohann et al 32 (2021) found that the absence of clinical information did not negatively impact the accuracy of radiological reports. In this study, 41% of Saudi radiologists seemed to believe that teleradiology has increased the quality of radiology reports during the pandemic, while the rest of the participants expressed uncertain views.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another disadvantage of teleradiology is worse supervision of the radiological examinations, because it limits the communication between the radiologist and radiographer. On the other hand, it should be mentioned that despite differences in setting and the lack of personal contact with the patient, radiographers, and other staff, a broad-scale German study [ 34 ] showed that the accuracy of teleradiologists is not significantly lower than in the case of on-site radiologists at on-call shifts.…”
Section: Deficiencies In the Polish Healthcare System And Radiologymentioning
confidence: 99%
“…The US military medical services uses digital radiology which is connected by a system of electronic health records. 9,10 The concept of dates back to the late 1920s. According to the definition of teleradiology by American College of Radiology (ACR), it is the electronic transmission of radiographic images from one location to another location for the purposes of radiographic interpretation and/or consultation.…”
Section: Tele Consultation Services In Radiologymentioning
confidence: 99%